2017
DOI: 10.1101/181313
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Putting the “dynamic” back into dynamic functional connectivity

Abstract: The study of fluctuations in time-resolved functional connectivity is a topic of substantial current interest. As the term "dynamic functional connectivity" implies, such fluctuations are believed to arise from dynamics in the neuronal systems generating these signals. While considerable activity currently attends to methodological and statistical issues regarding dynamic functional connectivity, less attention has been paid toward its candidate causes. Here, we review candidate scenarios for dynamic (function… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 115 publications
(148 reference statements)
0
19
0
Order By: Relevance
“…The occurrence of such bursts corresponds to a dynamical phenomenon known as metastability. In brief, for strong coupling, the system possesses a single, low-dimensional chaotic attractor that is embedded within the synchronization manifold: Although the dynamics of this chaotic attractor are reasonably complex (Supplementary Information I, Heitmann & Breakspear, 2018 ), both systems converge onto the same manifold, corresponding to stable (and stationary) generalized synchronization (Ashwin, 1995 ). The dynamics considered within the full (six-dimensional) space spanned by both systems become relatively simple.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of such bursts corresponds to a dynamical phenomenon known as metastability. In brief, for strong coupling, the system possesses a single, low-dimensional chaotic attractor that is embedded within the synchronization manifold: Although the dynamics of this chaotic attractor are reasonably complex (Supplementary Information I, Heitmann & Breakspear, 2018 ), both systems converge onto the same manifold, corresponding to stable (and stationary) generalized synchronization (Ashwin, 1995 ). The dynamics considered within the full (six-dimensional) space spanned by both systems become relatively simple.…”
Section: Resultsmentioning
confidence: 99%
“…The equation for the amplitude dynamics of a single node according to this simplified model are given by where r is the amplitude, λ and β are parameters that control the size and depth of the fixed-point and limit-cycle attractor basins. The parameters b 1 and b 2 control the influence of the additive ζ 1 and multiplicative noise ζ 2 x , respectively (see Supplementary Information III for full details; Heitmann & Breakspear, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This raises the question whether RSNs manifest only on longer time scales or whether they also 'exist' at shorter time scales. Recent studies of time-varying functional connectivity (tvFC; Heitmann and Breakspear, 2018;Lurie et al 2020;Kucyi et al 2018) have addressed the issue, approaching fine temporal structure and dynamics of FC through the use of shorter data samples, e.g. sliding windows or instantaneous co-activation patterns that result in temporally ordered sequences of functional networks and network states (Liu and Duyn 2013;Allen et al 2014;Shakil et al 2016;Preti et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Vidaurre et al (2017) showed, using a hidden Markov model, that the transitions between networks (states) are non-random. Two recent studies (Heitmann and Breakspear, 2017;Liégeois et al, 2017) also made the important point of distinguishing the meaning of "dynamic" from the statistical point of view (i.e., non-uniformity in time) from the link of these fluctuations to the intrinsic dynamics of neural populations that generate the recordings under examination.…”
Section: Introductionmentioning
confidence: 99%